ANALISIS HUBUNGAN TIPE KEPRIBADIAN DAN PERSEPSI DIMENSI DESAIN ORGANISASI TERHADAP TINGKAT STRES KERJA KARYAWAN BAGIAN IRONING DI PT.X - Chilvy Saputra; Ida Wahyuni; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Work stres is a pressure felt by someone who is experiencing emotions, thoughts and physical processes of a person where the pressure is caused by the work environment of individual is located. Job stres can be caused by organizational factors and non-organizational factors. The dimension of organizational design gives effect to job stres because of organizational design that determines an organization or company to run the process. One of the non-organizational factors that can cause work stres is the personality type. The purpose of this study was to analyze the relationship between personality type and perception of organizational design dimension with work stress. Variabels in this research was organizational design and personality type which affected  stres on employees. This study used cross sectional study . The population of the study was the Ironing worker, amounting to 39 people with the total population method. The result  of the research based on chi-square statistic test shows there was correlation between personality type and work stres (p = 0.003) and there was relation between perception of organizational design dimension with work stres (p = 0,016). To reduce the risk of work stres in workers it is advisable for the company to pursue an organizational design dimension that can unite the perceptions of every employee in the company to fit the design that the company has actually built.